Exploring EFL learners' use of web 2.0 tools: Preliminary findings - Kızıl, Aysel Şahin (My University, 2017)
The shift from ‘read only web’ to ‘read and write’ web has substantially changed the practices in the field of language education depending on the enormous potential of Web 2.0 technologies on language learning. However, understanding to what extent the language learners are aware of and proficient in using Web 2.0 tools remains a key consideration. Reporting on some preliminary results from a larger research project, this study aims to investigate the use of Web 2.0 tools by English as a Foreign Language (EFL) learners in their personal and educational life. Chosen through convenience sampling, the participants include 572 university level EFL learners. The data was collected through questionnaires and analysed using descriptive statistics. Suggesting a greater diversity with regard to the range and the proficiency in the use of Web 2.0 tools, the findings show that while established technologies such as searching for information or social networks are very popular among preparatory EFL learners, newer technologies including self-publishing and content creation tools are used by a rather small portion of the students.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Makale - Yabancı Dilde Makale
Keywords: EFL learners; Web 2.0; Learner perception; Information and communication technologies